Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

First hello all, we have a lecture. It has 10 questions but I'm stuck with these two about 3 hours and I can't solve them. Any help would be appreciated.

Question 1

Given that $T(1)=1$, and $T(n)=2T(\frac{n}{2})+1$, for $n$ a power of $2$, and greater than $1$. Using mathematical induction, prove that

$T(n) = 2^k.T(\frac{n}{2^k}) + 2^k - 1$

for $k=0, 1, 2, \dots, \log_2 n$.

Question 2

Definition: $H(j) = \frac{1}{1} + \frac{1}{2} + \frac{1}{3} + \dots + \frac{1}{j}$. Facts: $H(16) > 3.38$, $\frac{1}{3} + \frac{1}{4} = \frac{7}{12}, \frac{1}{4} + \frac{1}{5} + \frac{1}{7} = \frac{319}{420} $ a) Using induction on $n$, prove that $H(2^n) > 1 + 7n/12$, for $n\geq 4$.

share|improve this question
Welcome to math.SE: since you are new, I wanted to let you know a few things about the site. In order to get the best possible answers, it is helpful if you say in what context you encountered the problem, and what your thoughts on it are; this will prevent people from telling you things you already know, and help them give their answers at the right level. If this is homework, please add the homework tag; people will still help, so don't worry. –  Julian Kuelshammer Dec 1 '12 at 12:27
For some basic information about writing math at this site see e.g. here, here, here and here. –  Julian Kuelshammer Dec 1 '12 at 12:27

1 Answer 1

up vote 2 down vote accepted

1) Prove by induction on $k$:

If $0\le k\le m$, then $T(2^m)=2^kT(2^{m-k})+2^k-1$.

The case $k=0$ is trivial. If we already know that $T(2^m)=2^{k-1}T(2^{m-(k-1)})+2^{k-1}-1$ for all $m\ge k-1$, then for $m\ge 2^k$ we have $$\begin{align}T(2^m)&=2^{k-1}T(2^{m-(k-1)})+2^{k-1}-1\\ &=2^{k-1}\left(2\cdot T\left(\tfrac{2^{m-(k-1)}}2\right)+1\right)+2^{k-1}-1\\ &=2^k T(2^{m-k})+2^k-1\end{align}$$

2) Note that $$H(2(m+1))-H(2m)=\frac 1{2m+1}+\frac1{2(m+2)}>\frac2{2m+2}=H(m+1)-H(m)$$ and therefore (by induction on $d$) for $d>0$ $$H(2(m+d))-H(2m)>H(m+d)-H(m)$$ hence with $m=d=2^{n-1}$ $$H(2^{n+1})-H(2^n)>H(2^n)-H(2^{n-1})$$ thus by induction on $n$ $$H(2^n)-H(2^{n-1})>H(4)-H(2)=\frac7{12}\text{ if }n\ge2$$ and finally by induction on $n$ $$H(2^n)>H(16)+\frac7{12}(n-4)\text{ for }n\ge 4.$$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.